Various types and management of breast cancer: An overview - Ganesh N Sharma; Rahul Dave; Jyotsana Sanadya; Piush Sharma; K. K. Sharma (Wolters Kluwer Medknow Publications, 2010)
Now days, breast cancer is the most frequently diagnosed life-threatening cancer in women and the leading cause of cancer death among women. Since last two decades, researches related to the breast cancer has lead to extraordinary progress in our understanding of the disease, resulting in more efficient and less toxic treatments. Increased public awareness and improved screening have led to earlier diagnosis at stages amenable to complete surgical resection and curative therapies. Consequently, survival rates for breast cancer have improved significantly, particularly in younger women. This article addresses the types, causes, clinical symptoms and various approach both non- drug (such as surgery and radiation) and drug treatment (including chemotherapy, gene therapy etc.) of breast cancer.